[PP.32.17] THE EPIDEMIOLOGICAL CHARACTERISTIC OF HYPERHOMOCYSTEINEMIA AND H-TYPE HYPERTENSION IN THE ELDERLY IN BEIJING, CHINA. (September 2016) - Ma, L.; Li, L.; Tang, Z.; Li, Y.
Abstract : Objective: Hyperhomocysteinemia (HHcy) is an important risk factor of atherosclerosis-related diseases, and H-type hypertension (HHT) is obviously becoming a major health care concern in China. The aim of the study was to explore the prevalence of HHcy and HHT in the elderly in Beijing, China. Design and method: This is a retrospective study. Data for these analyses came from the Beijing Longitudinal Study of Ageing. This cross-sectional study comprised 1460 elderly people dwelling in an urban district, a suburb, and in mountain country in the general population in Beijing in 2012, which contained 638 male people and 822 female people. Statistical sampling techniques included cluster, stratification, and random selection. Basic information and physical examination were collected by trained staff, and the levels of plasma Homocysteine (Hcy) were measured. Results: Our results showed that the mean concentration of plasma Hcy was 21.3 umol/L in Beijing elderly population. 74.4% of the subjects were considered to have HHcy. 50.2% of the subjects were considered to have HHT. Conclusions: Our study findings indicated that the prevalence of HHcy and HHT were high in elderly participants in Beijing, China.